The effect of MemoVigor 2 on recent-onset idiopathic tinnitus: a randomized double-blind placebo-controlled clinical trial - Balatsouras, Dimitrios G.; Papitsi, Isidora; Koukoutsis, George; Katotomichelakis, Michael (Frontiers in Pharmacology, 2024)
Background: Tinnitus is a common symptom associated with the conscious perception of sound in the absence of a corresponding external or internal sound source, which can severely impact quality of life. Because of the current limited understanding of the precise pathophysiological mechanism of idiopathic tinnitus, no curable treatment has been attained yet. A food supplement trading as MemoVigor 2, which contains a combination of therapeutic ingredients with mainly antioxidant activity, has been used in the treatment of tinnitus. The objective of our study was to evaluate the effectiveness of MemoVigor 2 in the treatment of recent-onset idiopathic tinnitus.In a prospective single-centre randomized, double-blind, placebocontrolled clinical trial we studied 204 patients with idiopathic tinnitus divided into two groups: 104 patients who received MemoVigor 2 and 100 patients treated with placebo. To evaluate changes in tinnitus we used (1) audiometry/tympanometry; (2) specific measures of tinnitus perception, including tinnitus pitch, loudness at tinnitus pitch, loudness at 1 kHz, minimum masking level, and residual inhibition; (3) questionnaires of tinnitus handicap inventory, mini tinnitus questionnaire and patients' global impression of change. All patients underwent this test battery at the beginning of the study and in a repeat post-3-month session.Results: All tinnitus measures, including pitch, loudness, minimum masking level and residual inhibition improved significantly in the intervention group. Most of these measures improved in the placebo group too, but in a lesser degree. All questionnaire scores diminished significantly in both groups, but the degree of decrease was greater in the intervention group. The participants' tinnitus outcome reported after treatment using the patients' global impression of change score differed significantly between the two groups, with greater improvement observed in the intervention group.We found that the use of MemoVigor 2 improved recent-onset tinnitus, as proved by a set of tests performed for its evaluation, including audiometric measures, specific measures of tinnitus perception and tinnitus questionnaires. Tinnitus in the placebo group improved too, but to a lesser degree.